Development of new type of wound dressing based on cryogel matrix with incorporated nanoparticles - Saliev, Timur; Kulsharova, Gulsim; Akhmetova, Alma; Nurgozhin, Talgat; Whitby, Ray D.L. (The Materials Research Society of Japan (MRS-J), 2014)
A cryogel (polymethyl methacrylate) has been chosen as a basis for new type of wound dressings, where incorporated silver and gold nanoparticles do provide effective antibacterial protection [1]. This function will be enhanced by extracorporeal application of microwave radiation in safe regime.
Keywords: Wound dressing; Cryogel; Nanoparticles; Microwave